A Randomized Feasibility Trial of a Novel, Integrative, and Intensive Virtual Rehabilitation Program for Service Members Post-Acquired Brain Injury. Issue 1 (3rd July 2019) - Buccellato, Kiara H; Nordstrom, Michelle; Murphy, Justin M; Burdea, Grigore C; Polistico, Kevin; House, Gregory; Kim, Nam; Grampurohit, Namrata; Sorensen, Jeff; Isaacson, Brad M; Pasquina, Paul F
Abstract: Introduction: Acquired Brain Injury, whether resulting from Traumatic brain injury (TBI) or Cerebral Vascular Accident (CVA), represent major health concerns for the Department of Defense and the nation. TBI has been referred to as the "signature" injury of recent U.S. military conflicts in Iraq and Afghanistan – affecting approximately 380, 000 service members from 2000 to 2017; whereas CVA has been estimated to effect 795, 000 individuals each year in the United States. TBI and CVA often present with similar motor, cognitive, and emotional deficits; therefore the treatment interventions for both often overlap. The Defense Health Agency and Veterans Health Administration would benefit from enhanced rehabilitation solutions to treat deficits resulting from acquired brain injuries (ABI), including both TBI and CVA. The purpose of this study was to evaluate the feasibility of implementing a novel, integrative, and intensive virtual rehabilitation system for treating symptoms of ABI in an outpatient clinic. The secondary aim was to evaluate the system's clinical effectiveness. Materials and Methods: Military healthcare beneficiaries with ABI diagnoses completed a 6-week randomized feasibility study of the BrightBrainer Virtual Rehabilitation (BBVR) system in an outpatient military hospital clinic. Twenty-six candidates were screened, consented and randomized, 21 of whom completed the study. The BBVR system is an experimental adjunct ABI therapy program which utilizes virtual reality and repetitive bilateral upper extremity training. Four self-report questionnaires measured participant and provider acceptance of the system. Seven clinical outcomes included the Fugl-Meyer Assessment of Upper Extremity, Box and Blocks Test, Jebsen-Taylor Hand Function Test, Automated Neuropsychological Assessment Metrics, Neurobehavioral Symptom Inventory, Quick Inventory of Depressive Symptomatology-Self-Report, and Post Traumatic Stress Disorder Checklist- Civilian Version. The statistical analyses used bootstrapping, non-parametric statistics, and multilevel/hierarchical modeling as appropriate. This research was approved by the Walter Reed National Military Medical Center and Uniformed Services University of the Health Sciences Institutional Review Boards. Results: All of the participants and providers reported moderate to high levels of utility, ease of use and satisfaction with the BBVR system (x- = 73–86%). Adjunct therapy with the BBVR system trended towards statistical significance for the measure of cognitive function (ANAM [x- = −1.07, 95% CI −2.27 to 0.13, p = 0.074]); however, none of the other effects approached significance. Conclusion: This research provides evidence for the feasibility of implementing the BBVR system into an outpatient military setting for treatment of ABI symptoms. It is believed these data justify conducting a larger, randomized trial of the clinical effectiveness of the BBVR system.